2012
DOI: 10.1007/s10803-012-1467-2
|View full text |Cite
|
Sign up to set email alerts
|

Play and Joint Attention of Children with Autism in the Preschool Special Education Classroom

Abstract: The purpose of this study was to examine play and joint attention in children with autism (n=27) as compared to children with other developmental delays (n=28) in public preschool special education classrooms. The participants were observed in their classroom environment for 2 h over 3 separate days. Results show that children with autism spent more of their time unengaged and less time engaged in symbolic play and joint attention behaviors as compared to children with other developmental delays. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 37 publications
0
63
0
5
Order By: Relevance
“…Our study specifically focused on core deficits used within diagnosis and targeted within intervention (Drew et al 2002;Kasari et al 2006Kasari et al , 2010Kasari et al , 2008Lawton and Kasari 2012;Wong and Kasari 2012). While past research has been inconclusive surrounding gender differences for example in overall symptom severity (Hartley and Sikora 2009;Kirkovski et al 2013;McLennan et al 1993;Tsai and Beisler 1983;Van Wijngaarden-Cremers et al 2013), this study is one of the first attempts to explore specific behaviors known to associate with later outcomes, such as language development, in ASD (Charman 2003;Charman et al 2000;Kasari et al 2012Kasari et al , 2008Markus et al 2000;Mundy et al 1990;Toth et al 2006).…”
Section: Strengthsmentioning
confidence: 99%
“…Our study specifically focused on core deficits used within diagnosis and targeted within intervention (Drew et al 2002;Kasari et al 2006Kasari et al , 2010Kasari et al , 2008Lawton and Kasari 2012;Wong and Kasari 2012). While past research has been inconclusive surrounding gender differences for example in overall symptom severity (Hartley and Sikora 2009;Kirkovski et al 2013;McLennan et al 1993;Tsai and Beisler 1983;Van Wijngaarden-Cremers et al 2013), this study is one of the first attempts to explore specific behaviors known to associate with later outcomes, such as language development, in ASD (Charman 2003;Charman et al 2000;Kasari et al 2012Kasari et al , 2008Markus et al 2000;Mundy et al 1990;Toth et al 2006).…”
Section: Strengthsmentioning
confidence: 99%
“…Embora esse fenômeno possa ocorrer potencialmente com qualquer aluno, há uma vulnerabilidade específica no caso do autismo, que se refere à pobreza das habilidades sociocomunicativas, o que impacta diretamente as relações interpessoais com seus pares e professores (Semensato et al, 2010;Vargas, 2014;Wong & Kasari, 2012). Inclusive, relatos dão conta de que determinados eventos ocorridos na escola podem não ser relatados em casa, interrompendo as trocas entre esses ambientes (Arora, 1991).…”
Section: Envolvimento Parental E Transtorno Do Espectro Autistaunclassified
“…Chen et al provide insufficient evidence to draw such a radical conclusion. Although unusual eye gaze behavior is well-documented in individuals with autism [22,23], a tremendous amount of research has demonstrated that joint attention, eye contact, and eye gaze abnormalities can be ameliorated with existing research-based interventions and improvements in these behaviors are, in fact, associated with improvements in communication, social skills, and other desirable outcomes [24][25][26].…”
Section: Somamentioning
confidence: 99%